Cultural Representation in Erlangga Arabic Textbooks (Phases D–F): A Multimodal Discourse Analysis for the Merdeka Curriculum - Sholahudin, Shofwan; Alla, Mazin Abdelrazig Eljack Farag; Al Farisi, Mohamad Zaka (JOLLT Journal of Languages and Language Teaching, 2026)
Despite the Merdeka Curriculum’s emphasis on intercultural competence, the limited number of multimodal analyses of cultural representation in Arabic-language textbooks in Indonesia remains a concern. This study investigates how local, Arab–Islamic, and global cultural elements are represented in three Erlangga Arabic textbooks for Phases D–F using Multimodal Discourse Analysis (MDA) and the Multimodal Content Analysis (MMCA) template proposed by Serafini and Reid (2023). A total of 32 multimodal units were analysed. The findings reveal a clear imbalance in cultural representation. Local culture dominates across phases (75% in Phase D; 69.23% in Phase E; 72.73% in Phase F), while Arab–Islamic and global cultures are minimally represented. Big C cultural elements account for the vast majority of representations (over 85% within local culture), whereas small c elements appear only sporadically and exclusively within local contexts. Furthermore, most cultural representations are presented implicitly through visual–verbal integration rather than through explicit cultural explanation. These findings suggest that current Arabic language textbooks underrepresent cultural diversity and offer limited support for the development of intercultural communicative competence. The study recommends more balanced inclusion of local, Arab–Islamic, and global cultures, greater integration of small c cultural practices, and more explicit cultural framing to support teachers’ pedagogical mediation.